Electrolyte interference resistant solid heavy metal cation electrode, and preparation and use methods thereof

A solid heavy metal cation electrode with a nano-heavy metal coating and nanoporous polyvinyl chloride membrane addresses electrolyte interference, enabling accurate and real-time detection of heavy metal cations in water samples.

CN119198860APending Publication Date: 2024-12-27ZHEJIANG UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411308125.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing heavy metal ion detection technologies are limited by electrolyte interference, particularly in complex environmental water samples, which affects the accuracy of metal cation detection.

Method used

A solid heavy metal cation electrode is developed, comprising a heavy metal wire, a nano-heavy metal coating, a heavy metal/selenide or sulfide sensitive membrane, and a nanoporous polyvinyl chloride membrane, which shields against electrolyte interference and enhances detection accuracy.

Benefits of technology

The electrode provides accurate and real-time detection of heavy metal cations in various water media, resistant to electrolyte interference, with improved selectivity and extended service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198860A_ABST
    Figure CN119198860A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte interference resistant solid heavy metal cation electrode and a preparation and use method thereof, and belongs to the technical field of electrode preparation. The electrode sequentially comprises a heavy metal wire, a nano heavy metal coating, a heavy metal / selenide sensitive film or a heavy metal / sulfide sensitive film and a nano microporous polyvinyl chloride film from inside to outside. Firstly, a nanometer heavy metal coating is formed on the surface of a to-be-plated heavy metal wire through an electroplating method; placing in a sodium selenide solution or a sodium sulfide solution for chemical deposition reaction to generate a heavy metal / selenide sensitive film or a heavy metal / sulfide sensitive film to obtain a heavy metal ion selective electrode blank; vertically dipping in a film-forming agent, and standing vertically with the detection end facing upwards, so that a nano-microporous polyvinyl chloride film is generated on the surface; and finally, washing to remove the residual film-forming agent, and drying to obtain the electrolyte interference resistant solid heavy metal ion electrode. The electrode is firm in structure and small in size, is matched with a reference electrode for use, and is sensitive in response to metal ions in a solution to be detected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrode preparation, and in particular relates to a solid heavy metal cation electrode resistant to electrolyte interference, and a preparation and use method thereof. Background Art

[0002] As the main source of environmental pollution, heavy metal pollution poses a serious threat to the ecological environment and human health. They not only have a profound impact on terrestrial ecosystems, causing irreversible damage such as vegetation destruction and soil pollution, but can also penetrate into aquatic ecosystems through natural and artificial pathways. Once heavy metals enter the water, they will accumulate in sediments and aquatic organisms, and further amplify their ecological risks through the food chain, ultimately endangering the safety of human drinking water and the health of marine ecosystems.

[0003] In view of the severity and universality of heavy metal pollution, it is particularly important to accurately detect heavy metal ions in water in real time. Although the existing heavy metal ion detection technology has made some progress, there are still many limitations. In particular, the problem of electrolyte interference seriously limits the detection accuracy. For example, in practical applications, when the electrode method is selected for quantitative detection of metal cations, its accuracy is often affected by the interference of other electrolytes in the solution. Especially in the case of complex components of environmental water samples, the coexistence of multiple electrolytes will greatly interfere with the accurate determination of heavy metal cations. Therefore, it is urgent to provide a solid-state heavy metal cation electrode that can detect heavy metal cations in water in real time and is resistant to electrolyte interference. Summary of the invention

[0004] The purpose of the present invention is to address the deficiencies in the prior art and provide a solid heavy metal cation electrode resistant to electrolyte interference, and a preparation and use method.

[0005] The specific technical solutions adopted by the present invention are as follows:

[0006] In the first aspect, the present invention provides a solid heavy metal cation electrode resistant to electrolyte interference, which comprises, from the inside to the outside, a heavy metal wire as an electrode substrate, a nano-heavy metal coating, a heavy metal / selenide sensitive membrane or a heavy metal / sulfide sensitive membrane, and a nano-microporous polyvinyl chloride membrane.

[0007] The core of the electrode is the electrode substrate and connecting conductor. It is recommended to use a corresponding heavy metal wire with a diameter of 0.2 to 0.5 mm. The nano-metal coating on the metal wire forms a complete coating on the metal wire. The nano-metal particles have good conductivity. It acts as a conductive layer between the metal substrate and the outer sensitive film, replacing the role of the electrolyte solution in the liquid film electrode. At the same time, the nano-metal layer is prepared by in-situ growth, which is tightly combined with the metal wire and reduces the interface impedance.

[0008] The corresponding heavy metal sulfide is the core component of the heavy metal ion sensitive membrane. Heavy metal sulfide is a kind of insoluble salt. It exists in large quantities in seafloor hydrothermal deposits in nature and exists in dissolution-precipitation equilibrium with the corresponding heavy metal ions in the water medium. The concentration of heavy metal ions in the water body to be measured will cause the surface potential of the ion sensitive membrane material to change, forming a concentration response to the measured object; the relationship between the sulfide sensitive membrane and the nanometal layer is an in-situ composite relationship, and the response signal on the sensitive membrane can be transmitted to the substrate metal wire through the nanometal layer and detected by the sensor.

[0009] The nanoporous polyvinyl chloride (PVC) membrane located on the outermost layer of the electrode plays a shielding and protective role. Due to the presence of a large amount of dissolved salts in seawater, high concentrations of anions and cations will interfere with the selectivity of the heavy metal ion sensitive membrane to heavy metal ions in seawater. The nanoporous polyvinyl chloride (PVC) membrane coated on the surface of the electrode is hydrophobic and can block hydrophilic anions and cations outside the electrode without affecting the performance of the electrode, while heavy metal ions can selectively pass through. In addition, the nanoporous polyvinyl chloride (PVC) membrane can also slow down chemical corrosion and extend the service life of the electrode.

[0010] In a second aspect, the present invention provides a method for preparing a solid heavy metal cation electrode resistant to electrolyte interference, the specific steps are as follows:

[0011] S1: using an alternating current power supply, connecting the heavy metal wire to be plated to the negative electrode of the power supply, connecting the positive electrode of the power supply to the positive electrode of the diode, and connecting the negative electrode of the diode to the anode heavy metal wire; placing the heavy metal wire to be plated and the anode heavy metal wire in an electroplating solution, electroplating the heavy metal wire on the negative electrode of the power supply to generate a nano heavy metal coating; the electroplating solution uses a heavy metal chloride solution, a heavy metal nitrate solution or a heavy metal sulfide solution; the heavy metal components in the electroplating solution are consistent with those of the heavy metal wire to be plated and the anode heavy metal wire;

[0012] S2: placing the heavy metal wire with the nano heavy metal coating obtained in step S2 in a sodium selenide solution or a sodium sulfide solution, performing a chemical deposition reaction on the surface of the nano heavy metal coating to generate a heavy metal / selenide sensitive membrane or a heavy metal / sulfide sensitive membrane, and obtaining a heavy metal ion selective electrode embryo;

[0013] S3: Dipping the heavy metal ion selective electrode embryo obtained in step S2 into a film-forming agent and then taking it out, and standing it upright with the detection end facing upward, so that a nano-microporous polyvinyl chloride film is formed on the surface of the heavy metal ion selective electrode embryo; the solute in the film-forming agent is polyvinyl chloride, and the solvent is a mixture of tetrahydrofuran and cyclohexanone;

[0014] S4: placing the heavy metal ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step S3 in an extract to remove the residual film-forming agent; and obtaining a solid heavy metal cation electrode resistant to electrolyte interference after drying.

[0015] Preferably, the heavy metal chloride is cadmium chloride, cobalt chloride, copper chloride, nickel chloride, lead chloride or zinc chloride, the heavy metal nitrate is cadmium nitrate, cobalt nitrate, copper nitrate, nickel nitrate, lead nitrate or lead nitrate, and the heavy metal sulfate is cadmium sulfate, cobalt sulfate, copper sulfate, nickel sulfate, lead sulfate or lead sulfate; the diameter of the heavy metal wire to be plated is 0.2-0.5 mm.

[0016] Preferably, the concentration of heavy metal chloride or heavy metal nitrate in the electroplating solution is 3% to 10%.

[0017] Preferably, in step S1, the working parameters of the electroplating process are set as: sine wave, voltage 1.0-1.5V, frequency 50-100Hz, and electroplating time 50-100 seconds.

[0018] Preferably, in step S2, the concentration of the sodium selenide solution or the sodium sulfide solution is 0.01-0.1 M, the pH value is 9-10, and the chemical deposition reaction is carried out for 60-120 minutes.

[0019] Preferably, the mass ratio of tetrahydrofuran to cyclohexanone in the film-forming agent in step S3 is 1:(2-3); and the mass concentration of polyvinyl chloride in the film-forming agent is 5%-10%.

[0020] Preferably, in step S3, the heavy metal ion selective electrode embryo is placed vertically in the film-forming agent for 10 to 30 minutes; the extractant in step S4 is methanol or ethanol, and the heavy metal ion selective electrode embryo after the reaction is placed in methanol or ethanol for washing for 5 to 15 minutes.

[0021] In a third aspect, the present invention provides a solid heavy metal cation electrode resistant to electrolyte interference prepared by the preparation method of the solid heavy metal cation electrode described in the second aspect.

[0022] In a fourth aspect, the present invention provides a method for using a solid heavy metal cation electrode resistant to electrolyte interference, wherein the solid heavy metal cation electrode described in the first aspect or the third aspect is used as a working electrode, and Ag / Ag 2 Se or Ag / Ag 2 The S electrode is used as a reference electrode; the working electrode and the reference electrode are both placed in a water body to be tested containing heavy metal cations, and the potential difference between the working electrode and the reference electrode is measured; the concentration of the heavy metal cations in the solution to be tested is obtained by conversion through a calibration formula.

[0023] Usually, the ion selective electrode uses Ag / AgCl electrode as the reference electrode, but in the environment with high ionic strength, such as seawater, salt lake and other high salinity environments, the dissolved Cl in the water - Ions will form a response on the Ag / AgCl electrode, interfering with the potential signal between the reference electrode and the working electrode. In addition, carbonate, sulfate, phosphate, which are common in natural water bodies, and hydrogen sulfide in reducing water bodies, can all combine with silver, and the solubility product of the chemical formed is higher than that of silver chloride. Therefore, they can interfere with the Ag / AgCl electrode and corrode the sensitive membrane of the electrode. 2 The solubility product of Se is 63.7, Ag 2 The solubility product of S is 50.1, which is much higher than other silver salt compounds. 2 Se or Ag / Ag 2 The S electrode is the reference electrode, and theoretically, it is less likely to be interfered by other anions. 2 Se, Ag / Ag 2 The theoretical basis for the electrode pair with S electrode as reference electrode to have higher resistance to electrolyte interference.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The heavy metal cation electrode resistant to electrolyte interference provided by the present invention is a fully solid structure and does not contain an internal reference electrolyte solution. The electrode is compact and has a solid structure. The outermost nanoporous polyvinyl chloride membrane can shield the interference of water-soluble electrolytes on the ion-selective membrane.

[0026] (2) In terms of usage, Ag / Ag 2 Se or Ag / Ag 2 The S electrode is a reference electrode, which avoids the interference of chloride ions and other anions in the water body on the reference electrode, thereby improving the anti-interference ability of the detection electrode pair. The heavy metal cation electrode provided by the present invention and the matching reference electrode are suitable for detecting the heavy metal cation content in various water media, and have a wide range of uses in water environment monitoring, real-time online detection in the field of chemistry and chemical engineering, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope image of the solid copper ion electrode prepared in Example 1, with a magnification of 150 times;

[0028] Figure 2 This is a scanning electron microscope image of the solid copper ion electrode prepared in Example 1, with a magnification of 10,000 times;

[0029] Figure 3The EDS energy spectrum analysis result of the surface of the solid copper ion electrode prepared in Example 1;

[0030] Figure 4 The solid copper ion electrode in Example 2 is 10 -1 M, 10 -2 M, 10 -3 M, 10 -4 M, 10 -5 M C 2+ Calibration results in solution;

[0031] Figure 5 is the calibration curve in Example 2;

[0032] Figure 6 This is the test result of the solid copper ion electrode on the copper element standard solution in Example 2. DETAILED DESCRIPTION

[0033] The present invention is further described and illustrated below in conjunction with the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly without conflicting with each other.

[0034] Example 1

[0035] This embodiment provides a method for preparing a solid copper ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0036] (1) Cut a silver wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the silver wire with sandpaper with a polishing degree of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean it in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, use dust-free paper to absorb the surface moisture. Use a function signal generator as a power supply, connect the silver wire to the negative pole of the function signal generator, connect the positive pole to the positive pole of the diode, and connect the negative pole of the diode to the anode silver wire. The silver wire to be plated and the anode silver wire are placed in a silver nitrate solution with a concentration of 0.01M. The working parameters are set as: sine wave, voltage 0.5V, frequency 50Hz, electroplating time 100 seconds, and obtain a silver wire with nanosilver plated on the surface. Ag is generated on the surface of nanosilver 2 The part electroplated with nanosilver was immersed in a 0.05M sodium sulfide solution (pH=10) for 60 minutes to form Ag on the surface of the nanosilver. 2 S film, washed with deionized water and dried to obtain Ag / Ag 2 S reference electrode.

[0037] (2) Cut a copper wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the copper wire with sandpaper of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean the wire in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, use dust-free paper to absorb the surface moisture. Dissolve 0.08g of copper sulfate in 10g of deionized water and stir until completely dissolved to obtain a plating solution with a concentration of 0.05M.

[0038] A function signal generator is used as a power source, the copper wire to be plated is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, the negative pole of the diode is connected to the anode copper wire, the copper wire to be plated and the anode copper wire are both placed in the prepared electroplating solution, and the working parameters are set as: sine wave, voltage 1.5V, frequency 50Hz, electroplating time 120 seconds, to obtain a copper wire with a nano-copper coating on the surface.

[0039] (3) The copper wire with the nano copper coating is immersed in a sodium sulfide solution (pH=10) with a concentration of 0.01 M for 120 minutes to perform a chemical deposition reaction on the surface of the nano heavy metal coating to form a copper sulfide sensitive film on the surface of the nano copper coating. The copper wire is washed with deionized water and dried to obtain a copper ion selective electrode embryo.

[0040] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:2 to obtain a mixed solvent. 0.5 g of polyvinyl chloride (PVC) is added to 9.5 g of the mixed solvent and magnetically stirred until completely dissolved to obtain a film-forming agent with a concentration of 5%. The copper ion selective electrode embryo is dipped in the film-forming agent and allowed to stand upright with the detection end facing upward for 20 minutes to form a nanoporous polyvinyl chloride film on the surface of the copper ion selective electrode embryo.

[0041] (5) The copper ion selective electrode embryo with nanoporous polyvinyl chloride membrane is immersed in ethanol for 10 minutes to remove the residual film-forming agent. After drying, a solid copper cation electrode resistant to electrolyte interference is obtained.

[0042] The solid copper cation electrode resistant to electrolyte interference prepared in Example 1 was subjected to scanning electron microscopy and energy spectrum analysis:

[0043] Figure 1 This is a scanning electron microscope image of the solid-state copper ion electrode that is resistant to electrolyte interference. The magnification is 150 times, and the overall morphology of the copper wire electrode can be seen; Figure 2 The surface of the solid copper ion electrode is magnified 10,000 times. It can be observed that the surface of the copper wire is covered with a layer of sensitive film material, which is composed of a stack of 1-5 μm-sized flake structures. There are a large number of gaps between the different flakes, which represents the larger specific surface area of ​​the electrode. Figure 3The EDS energy spectrum analysis results of the surface of the solid copper ion electrode resistant to electrolyte interference show that the elements of the flake structure are Cu and S, indicating that the sensitive film component on the surface of the copper wire is CuS.

[0044] Example 2

[0045] This embodiment provides a method for using the solid copper ion electrode resistant to electrolyte interference prepared in Embodiment 1, which is specifically as follows:

[0046] (1) The copper ion concentration is 10 -1 M, 10 -2 M, 10 -3 M, 10 -4 M, 10 -5 The standard solution is prepared using Dickson seawater.

[0047] Dickson seawater composition: total dissolved inorganic carbon (total carbonate) 2031.90±0.32μM, total alkalinity 2231.59±0.62μM, phosphate 0.25μM, silicate 1.6μM, nitrate 0.99μM.

[0048] (2) Using the solid copper ion electrode as the working electrode, the Ag / Ag 2 The S electrode was used as the reference electrode to test the above standard solutions. The test time of each standard solution was 60s, and the potential difference between the working electrode and the reference electrode was measured. The potential difference was linearly related to the copper ion concentration in the standard solution, and the calibration formula was obtained as E = 28.46lg (Cu 2+ )+110.56mV,R 2 =0.9994.

[0049] like Figure 4 As shown in the figure, it can be seen that the copper ion selective electrode responds very quickly (<3s) in copper ion solutions with various electrolytes and has good stability. Figure 5 As shown, the solid copper ion electrode has different concentrations of Cu 2+ The Nernst linear response in the solution is good, with a slope of 28.46 mV / dec (the ideal Nernst slope value of divalent cations is 29.59 mV / dec), R 2 =0.9994.

[0050] (3) Using the solid copper ion electrode as the working electrode, the Ag / Ag 2 The S electrode is used as the reference electrode for Cu 2+ The test was conducted with a copper standard solution having a concentration of 1000ug / mL (0.0157M). The copper standard solution was purchased from Shanghai Aladdin Reagent Co., Ltd.

[0051] The stable data value of the solid copper ion electrode is determined by a change of less than 1mV within 1 minute. 2+ The voltage of the 0.0157M standard solution sample when it is stable is 58.9mV. Substituting into the formula E=28.46lg(Cu 2+ )+110.56mV(R 2 =0.9994), we can get the Cu in the measured solution 2+ The concentration is about 0.0153 M. Compared with the known concentration of 0.0157 M, the measured difference of the electrode is 0.0004 M, and the relative error is 2.5%. This shows that the solid copper ion electrode resistant to electrolyte interference prepared by the present invention can perform online copper ion detection with high sensitivity and high selectivity.

[0052] Example 3

[0053] This embodiment provides a method for preparing a solid copper ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0054] (1) Cut a 40 mm long 0.5 mm diameter cadmium wire and polish the surface of the cadmium wire with sandpaper of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean the wire in 0.1 M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, dry the surface moisture with dust-free paper. Dissolve 1 g of cadmium nitrate in 9 g of ethylene glycol and stir until completely dissolved to obtain a plating solution with a concentration of 10%.

[0055] (2) Using a function signal generator as a power source, the wire to be plated with cadmium is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, and the negative pole of the diode is connected to the anode cadmium wire. The wire to be plated with cadmium and the anode cadmium wire are placed in the prepared electroplating solution. The working parameters are set as follows: sine wave, voltage 1.5V, frequency 100Hz, electroplating time 50 seconds, and a cadmium wire with a nano-cadmium coating on the surface is obtained.

[0056] (3) The copper wire with the nano-cadmium coating is immersed in a 0.05M sodium selenide solution (pH=10) for 5 minutes to perform a chemical deposition reaction on the surface of the nano-heavy metal coating to form a cadmium selenide sensitive film on the surface of the nano-copper coating. The copper wire is washed with deionized water and dried to obtain a cadmium ion selective electrode embryo.

[0057] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:2 to obtain a mixed solvent. 0.5 g of polyvinyl chloride (PVC) is added to 9.5 g of the mixed solvent and stirred magnetically until completely dissolved to obtain a film-forming agent with a concentration of 5%. The cadmium ion selective electrode embryo is dipped in the film-forming agent and allowed to stand upright with the detection end facing upward for 20 minutes to form a nanoporous polyvinyl chloride film on the surface of the cadmium ion selective electrode embryo.

[0058] (5) Immerse the cadmium ion selective electrode embryo with nanoporous polyvinyl chloride membrane in methanol for 15 minutes to remove the residual film-forming agent. After drying, obtain a solid cadmium cation electrode resistant to electrolyte interference.

[0059] Example 4

[0060] This embodiment provides a method for preparing a solid cobalt ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0061] (1) Cut a cobalt wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the cobalt wire with sandpaper of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean it in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, use dust-free paper to absorb the surface moisture. Dissolve 0.3g of cobalt chloride in 9.7g of propylene glycol and stir until completely dissolved to obtain a plating solution with a concentration of 3%.

[0062] (2) Using a function signal generator as a power source, the cobalt wire to be plated is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, and the negative pole of the diode is connected to the anode cobalt wire. The cobalt wire to be plated and the anode cobalt wire are both placed in the prepared electroplating solution. The working parameters are set as follows: sine wave, voltage 1.0V, frequency 50Hz, electroplating time 100 seconds, and a cobalt wire with a nano-cobalt coating on the surface is obtained.

[0063] (3) The cobalt wire with the nano-cobalt coating is immersed in a 0.1 M sodium selenide solution (pH = 10) for 30 minutes to perform a chemical deposition reaction on the surface of the nano-heavy metal coating to form a cobalt selenide sensitive film on the surface of the nano-cobalt coating. The cobalt wire is washed with deionized water and dried to obtain a cobalt ion selective electrode embryo.

[0064] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:3 to obtain a mixed solvent. 1 g of polyvinyl chloride (PVC) is added to 9 g of the mixed solvent and stirred magnetically until completely dissolved to obtain a film-forming agent with a concentration of 10%. The film-forming agent is dipped into a cobalt ion selective electrode embryo and allowed to stand upright for 30 minutes with the detection end facing upward, so that a nanoporous polyvinyl chloride film is formed on the surface of the cobalt ion selective electrode embryo.

[0065] (5) The cobalt ion selective electrode embryo with nanoporous polyvinyl chloride membrane is immersed in ethanol for 15 minutes to remove the residual film-forming agent. After drying, a solid cobalt cation electrode resistant to electrolyte interference is obtained.

[0066] Example 5

[0067] This embodiment provides a method for preparing a solid nickel ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0068] (1) Cut a nickel wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the nickel wire with sandpaper of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean the wire in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, use dust-free paper to absorb the surface moisture. Dissolve 0.6g of nickel nitrate in 9.4g of propylene glycol and stir until completely dissolved to obtain a plating solution with a concentration of 6%.

[0069] (2) Using a function signal generator as a power source, the wire to be nickel-plated is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, the negative pole of the diode is connected to the anode nickel wire, the wire to be nickel-plated and the anode nickel wire are placed in the prepared electroplating solution, and the working parameters are set as follows: sine wave, voltage 1.3V, frequency 80Hz, electroplating time 80 seconds, to obtain a nickel wire with a nano-nickel coating on the surface.

[0070] (3) The nickel wire with the nano-nickel coating is immersed in a sodium sulfide solution (pH=10) with a concentration of 0.06 M for 60 minutes to perform a chemical deposition reaction on the surface of the nano-heavy metal coating to form a nickel sulfide sensitive film on the surface of the nano-nickel coating. The nickel wire is washed with deionized water and dried to obtain a nickel ion selective electrode embryo.

[0071] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:3 to obtain a mixed solvent. 1 g of polyvinyl chloride (PVC) is added to 9 g of the mixed solvent and stirred magnetically until completely dissolved to obtain a film-forming agent with a concentration of 10%. The nickel ion selective electrode embryo is dipped into the film-forming agent solution and allowed to stand upright with the detection end facing upward for 20 minutes to form a nanoporous polyvinyl chloride film on the surface of the cobalt ion selective electrode embryo.

[0072] (5) The cobalt ion selective electrode embryo with nanoporous polyvinyl chloride membrane was immersed in methanol for 8 minutes to remove the residual film-forming agent. After drying, a solid nickel cation electrode resistant to electrolyte interference was obtained.

[0073] Example 6

[0074] This embodiment provides a method for preparing a solid cobalt ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0075] (1) Cut a lead wire with a length of 40 mm and a diameter of 0.5 mm. Place it in 0.1M nitric acid solution, acetone and ultrapure water for ultrasonic cleaning for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, use dust-free paper to absorb the surface moisture. Dissolve 0.8g of lead nitrate in 9.2g of ethylene glycol and stir until completely dissolved to obtain an electroplating solution with a concentration of 8%.

[0076] (2) Using a function signal generator as a power source, the lead wire to be plated is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, the negative pole of the diode is connected to the anode lead wire, the lead wire to be plated and the anode lead wire are placed in the prepared electroplating solution, and the working parameters are set as: sine wave, voltage 1.2V, frequency 60Hz, electroplating time 60 seconds, to obtain a lead wire with a nano-lead coating on the surface.

[0077] (3) Immersing the lead wire with the nano-lead coating in a 0.08 M sodium sulfide solution (pH=10) for 40 minutes, performing a chemical deposition reaction on the surface of the nano-heavy metal coating, forming a lead sulfide sensitive film on the surface of the nano-lead coating, and washing with deionized water and drying to obtain a lead ion selective electrode embryo.

[0078] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:2 to obtain a mixed solvent; 0.5 g of polyvinyl chloride (PVC) is added to 9.5 g of the mixed solvent, and magnetic stirring is performed until it is completely dissolved to obtain a film-forming agent with a concentration of 5%. The lead ion selective electrode embryo is dipped in the film-forming agent, and the electrode is placed upright with the detection end facing upward for 25 minutes to form a nanoporous polyvinyl chloride film on the surface of the lead ion selective electrode embryo.

[0079] (5) The lead ion selective electrode embryo with nanoporous polyvinyl chloride membrane is immersed in ethanol for 12 minutes to remove the residual film-forming agent. After drying, a solid lead cation electrode resistant to electrolyte interference is obtained.

[0080] Example 7

[0081] This embodiment provides a method for preparing a solid zinc ion electrode resistant to electrolyte interference, and the specific steps are as follows:

[0082] (1) Cut a zinc wire with a length of 40 mm and a diameter of 0.5 mm, and polish the surface of the zinc wire with sandpaper of 1000 mesh and 5000 mesh respectively. After polishing, ultrasonically clean the wire in 0.1M nitric acid solution, acetone and ultrapure water for 10 minutes to remove the oxide layer and oil stains on the metal surface. After cleaning, dry the surface moisture with dust-free paper. Dissolve 0.6g zinc nitrate in 9.4g propylene glycol and stir until completely dissolved to obtain a plating solution with a concentration of 6%.

[0083] (2) Using a function signal generator as a power source, the wire to be galvanized is connected to the negative pole of the function signal generator, the positive pole is connected to the positive pole of the diode, and the negative pole of the diode is connected to the anode zinc wire. The wire to be galvanized and the anode zinc wire are placed in the prepared electroplating solution. The working parameters are set as follows: sine wave, voltage 1.1V, frequency 90Hz, electroplating time 90 seconds, and a zinc wire with a nano zinc coating on the surface is obtained.

[0084] (3) The zinc wire with the nano zinc coating is immersed in a 0.06 M sodium selenide solution (pH = 10) for 40 minutes to perform a chemical deposition reaction on the surface of the nano heavy metal coating to form a zinc selenide sensitive film on the surface of the nano zinc coating. The zinc wire is washed with deionized water and dried to obtain a zinc ion selective electrode embryo.

[0085] (4) Cyclohexanone and tetrahydrofuran are mixed in a mass ratio of 1:3 to obtain a mixed solvent. 1 g of polyvinyl chloride (PVC) is added to 9 g of the mixed solvent and stirred magnetically until completely dissolved to obtain a film-forming agent with a concentration of 10%. The zinc ion selective electrode embryo is dipped into the film-forming agent solution and allowed to stand upright with the detection end facing upward for 15 minutes to form a nanoporous polyvinyl chloride film on the surface of the zinc ion selective electrode embryo.

[0086] (5) The zinc ion selective electrode embryo with nanoporous polyvinyl chloride membrane is immersed in ethanol for 15 minutes to remove the residual film-forming agent. After drying, a solid zinc cation electrode resistant to electrolyte interference is obtained.

[0087] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A solid heavy metal cation electrode resistant to electrolyte interference, characterized in that: From the inside to the outside, there are heavy metal wires as electrode substrates, nano heavy metal coatings, heavy metal / selenide sensitive membranes or heavy metal / sulfide sensitive membranes and nano-microporous polyvinyl chloride membranes.

2. A method for preparing a solid heavy metal cation electrode resistant to electrolyte interference, characterized in that: The specific steps are as follows: S1: using an alternating current power supply, connecting the heavy metal wire to be plated to the negative electrode of the power supply, connecting the positive electrode of the power supply to the positive electrode of the diode, and connecting the negative electrode of the diode to the anode heavy metal wire; placing the heavy metal wire to be plated and the anode heavy metal wire in an electroplating solution, electroplating the heavy metal wire on the negative electrode of the power supply to generate a nano heavy metal coating; the electroplating solution uses a heavy metal chloride solution, a heavy metal nitrate solution or a heavy metal sulfide solution; the heavy metal components in the electroplating solution are consistent with those of the heavy metal wire to be plated and the anode heavy metal wire; S2: placing the heavy metal wire with the nano heavy metal coating obtained in step S2 in a sodium selenide solution or a sodium sulfide solution, performing a chemical deposition reaction on the surface of the nano heavy metal coating to generate a heavy metal / selenide sensitive membrane or a heavy metal / sulfide sensitive membrane, and obtaining a heavy metal ion selective electrode embryo; S3: Dipping the heavy metal ion selective electrode embryo obtained in step S2 into a film-forming agent and then taking it out, and standing it upright with the detection end facing upward, so that a nano-microporous polyvinyl chloride film is formed on the surface of the heavy metal ion selective electrode embryo; the solute in the film-forming agent is polyvinyl chloride, and the solvent is a mixture of tetrahydrofuran and cyclohexanone; S4: placing the heavy metal ion selective electrode embryo with nanoporous polyvinyl chloride membrane obtained in step S3 in an extract to remove the residual film-forming agent; and obtaining a solid heavy metal cation electrode resistant to electrolyte interference after drying.

3. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: The heavy metal chloride is cadmium chloride, cobalt chloride, copper chloride, nickel chloride, lead chloride or zinc chloride, the heavy metal nitrate is cadmium nitrate, cobalt nitrate, copper nitrate, nickel nitrate, lead nitrate or lead nitrate, and the heavy metal sulfate is cadmium sulfate, cobalt sulfate, copper sulfate, nickel sulfate, lead sulfate or lead sulfate; the diameter of the heavy metal wire to be plated is 0.2-0.5 mm.

4. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: The concentration of heavy metal chloride or heavy metal nitrate in the electroplating solution is 3% to 10%.

5. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: In step S1, the working parameters of the electroplating process are set as: sine wave, voltage 1.0-1.5V, frequency 50-100Hz, and electroplating time 50-100 seconds.

6. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: In step S2, the concentration of the sodium selenide solution or the sodium sulfide solution is 0.01-0.1 M, the pH value is 9-10, and the chemical deposition reaction is carried out for 60-120 minutes.

7. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: The mass ratio of tetrahydrofuran to cyclohexanone in the film-forming agent in step S3 is 1:(2-3); the mass concentration of polyvinyl chloride in the film-forming agent is 5%-10%.

8. The method for preparing a solid heavy metal cation electrode according to claim 2, characterized in that: In step S3, the heavy metal ion selective electrode embryo is vertically placed in a film-forming agent for 10 to 30 minutes; in step S4, the extractant is methanol or ethanol, and the heavy metal ion selective electrode embryo after the reaction is placed in methanol or ethanol for washing for 5 to 15 minutes.

9. A solid heavy metal cation electrode resistant to electrolyte interference prepared by the method for preparing a solid heavy metal cation electrode according to any one of claims 2 to 8.

10. A method for using a solid heavy metal cation electrode resistant to electrolyte interference, characterized in that: The solid heavy metal cation electrode according to claim 1 or 9 is used as a working electrode, and the Ag / Ag2Se or Ag / Ag2S electrode is used as a reference electrode; the working electrode and the reference electrode are both placed in a water body to be detected containing heavy metal cations, and the potential difference between the working electrode and the reference electrode is measured; The concentration of heavy metal cations in the solution to be tested is calculated using the calibration formula.

Citation Information

Cited By

  • Preparation method of silver selenide three-dimensional structure thermoelectric material

    CN120210907A